Hierarchical Modeling of Archaeological and Modern Flax Fiber: From Micro- to Macroscale - Vasuki Rajakumaran; Johnny Beaugrand; Alessia Melelli; Mario Scheel; Timm Weitkamp; Jonathan Perrin; Alain Bourmaud; Henry Proudhon; Sofiane Guessasma (Fibers, 2025)
Flax fiber reinforcements weaken with aging and microstructural changes, limiting their applications. Here, we examine the effects of microstructure and aging on flax fiber elements’ performance by using 4000-year-old and modern Egyptian flax as references through multi-scale numerical modeling. This study introduces a novel investigation into the tensile stress distribution behavior of archaeological and modern flax yarns. The finite element (FE) model is derived from 3D volumes obtained via X-ray microtomography and tensile testing in the elastic domain. At the microscale, fibers exhibit higher axial stress concentrations around surface defects and pores, particularly in regions with kink bands and lumens. At the mesoscale, fiber bundles show increased stress concentrations at inter-fiber voids and lumen, with larger bundles exhibiting greater stress heterogeneity, especially around pores and surface roughness. At the macroscale, yarns display significant stress heterogeneity, especially around microstructural defects like pores and fiber–fiber cohesion points. Aged fibers from ancient Egyptian cultural heritage in particular demonstrate large fiber discontinuities due to long-term degradation or aging. These numerical observations highlight how porosity, surface imperfections, and structural degradation increase stress concentration, leading to fiber rupture and mechanical failure. This insight reveals how aging and defects impact flax fiber performance and durability.